Rational Design and Synthesis of Porous Organic−Inorganic Hybrid Frameworks Constructed by 1,3,5-Benzenetriphosphonic Acid and Pyridine Synthons - Kong, Deyuan; Zoñ, Jerzy; McBee, Jennifer; Clearfield, Abraham (Inorganic chemistry, 2006)
1,3,5-Benzenetriphosphonic acid, H6BTP, 1,3,5-[(HO)2OP]3C6H3, was reacted hydrothermally with copper salts in the absence and presence of 4,4‘-bipyridine (bpy) and 4,4‘-trimethlyenedipyridine (tbpy) in a 1:1 molar ratio leading to three new organic−inorganic hybrid frameworks. Compound 1, {Cu6[C6H3(PO3)3]2(H2O)8}·5.5H2O, has three different copper ions that are interconnected by the highly charged [1,3,5-(PO3)3C6H3]6- anionic moieties. These moieties self-assemble through tetra-copper units to give a cagelike motif with two benzene rings parallel to each other at a distance of 3.531 Å which extend along the a axis and link with a grouping of four-coordinated copper units in the b axis direction to give the cross-linked layered structure. In compound 2, Cu{C6H3[PO(OH)O]2[PO(OH)2]}(C10H8N2), the copper ions are in square pyramidal geometries and are interconnected via chelating and bridging BTP ligands into layers which are further cross-linked by bpy ligands into a pillared layered architecture. Compound 3, {Cu2C6H3[PO(OH)O]2[PO3](C13H14N2)}·3H2O·0.5HCON(CH3)2, contains tetra-copper units that are linked by BTP ligands and further linked by tbpy linkers in the c axis direction to produce a large channel-sized 3D framework.